Forms of Art Presentation Tari Kuda Lumping In the village Manunggal Karya Subdistrict Randangan, Pohuwato Regency - Gilang Pratama Ismail; Nurlia Djafar; Trubus Semiadji; Mimy Astuti Pulukadang; Laode Karlan (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
This study aims to describe the presentation form and analyze the correlation between the elements that form the Kuda Lumping dance in Manunggal Karya Village, Randangan District, Pohuwato Regency. This research is motivated by the existence of traditional Javanese art that is still preserved and purely maintained by the transmigrant community since 1981, and functions as a cultural identity and unifier of society. The method used is descriptive qualitative with an ethnographic approach. Data collection was carried out through participatory observation, in-depth interviews, and documentation studies. Data analysis refers to the model of data reduction, data presentation, and conclusion drawing. The results show that the presentation form of the Kuda Lumping dance is divided into two main acts, namely the opening act featuring seven structured movements, and the main act which is full of mystical nuances with the phenomenon of spirit possession. The elements that form the performance include movement, floor patterns, makeup and costumes, accompanying music, properties, and the performance venue which are closely correlated to form a unified meaning. The main uniqueness lies in the self-flagellation and the involvement of the audience, who are possessed by spirits. This art form carries philosophical meanings of spiritual strength, character building, and community unification. This art form is a clear demonstration of harmonious cultural acculturation, where Javanese culture remains preserved and fully accepted within the Gorontalo cultural context.